Quedancor pro-farmer focus profiles of the farmer beneficiaries of the Barangay Marketing Center Program. (Produced by the Promotions and Publications, 1996)
Contents: CBMC profiles. FLGC profiles. Programs primer. Map of CBMCs/FLGCs in the countryside.